POSITIVE RADIAL, SOLUTIONS OF CERTAIN SEMILINEAR ELLIPTIC EQUATIONS IN ANNULAR DOMAINS - Vrdoljak, B. (Matematichki Bilten, 1995)
In this paper it is established the existence, behaviour and approximation of positive radially symmetric solutions of semilinear elliptic equation (1) in an annulus \(Ω\), when \(λ\) and \(F\) satisfy the corresponding sufficient conditions.